Antifreeze Proteins: An Inovative Agent for the Prevention of Foods - İlhan Gün; Aslı Albayrak; Asuman Gürsel (Turkish Journal of Agriculture: Food Science and Technology)
Antifreeze proteins are those proteins that have ability to protect the organism against environmental conditions at temperatures below zero, and to resize the shape and size of ice crystals. Due to these properties, they prevent food from sensory, structural and mechanical damages during the storage in cold and they extend the product shelf life. In this review, the types and structure of antifreeze proteins, their mechanism of action and the possibilities of use in food are presented.